Care Planning Meetings: Issues for Policy, Multi-disciplinary Practice and Patient Participation. Issue 1 (1st January 2018) - Donnelly, Sarah; Cahill, Suzanne; O'Neill, Desmond
Abstract : Although Care-Planning Meetings (CPMs) are an increasingly common part of the practice of social work with older people and multi-disciplinary teamwork, it is uncertain how and by whom the voice and wishes of older people, including those with a cognitive impairment, are given due priority. In addition, there is little professional guidance as to how to best plan and facilitate CPMs for older patients with cognitive and communication deficits and other often complex needs. An added challenge is the wide, often diverse and conflicting range of perspectives held by health and social care professionals and other family members who may be involved. This scoping review article on CPMs for older people, considers the facilitators and barriers to effective participation as identified in the literature and proposes suggestions for best practices in CPMs which could help promote an individualised approach to participation that best reflects the older patient's wishes.